Modelling of shockwave propagation in orthotropic materials - Mohd Nor, Mohd Khir; Vignjevic, Rade; Campbell, James (Trans Tech Publications, 2013)
Modelling of shockwave propagation in orthotropic materials requires an appropriate description of material behaviour within elastic and plastic regimes. To deal with this issues, a finite strain constitutive model for orthotropic materials was developed within a consistent thermodynamic framework of irreversible process in this paper. The important features of this material model are the multiplicative decomposition of the deformation gradient and a Mandel stress tensor combined with the new stress tensor decomposition generalised for orthotropic materials. The elastic free energy function and the yield function are defined within an invariant theory by means of the introduction of the structural tensors. The plastic behaviour is characterised within the associative plasticity framework using the Hill’s yield criterion. The complexity was further extended by coupling the formulation with the equation of state (EOS) to control the response of the material to shock loading. This material model which was developed and integrated in the isoclinic configuration provides a unique treatment for elastic and plastic anisotropy. The effects of elastic anisotropy are taken into account through the stress tensor decomposition and plastic anisotropy through yield surface defined in the generalized deviatoric plane perpendicular to the generalised pressure. To test its ability to describe shockwave propagation, the new material model was implemented into the LLNL-DYNA3D code. The results generated by the proposed material model were compared against the experimental Plate Impact test data of Aluminium Alloy 7010. A good agreement between experimental and simulation was obtained for two principal directions of material orthotropy.